2008
DOI: 10.1530/eje-08-0311
|View full text |Cite
|
Sign up to set email alerts
|

An adrenal rest tumour in the perirenal region in a patient with congenital adrenal hyperplasia due to congenital 3β-hydroxysteroid dehydrogenase deficiency

Abstract: Background: In contrast to the high incidence of testicular adrenal rest tumours (TART) in adult male patients with congenital adrenal hyperplasia (CAH), ovarian adrenal rest tumours in female CAH patients are very rare and other locations of adrenal rest tumours have never been reported. Here, we report on an adult patient with CAH due to 3b-hydroxysteroid dehydrogenase (HSD) deficiency with bilateral TART and additionally a large perirenal adrenal rest tumour. Case report: The patient was known with CAH due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
1
11
0
5
Order By: Relevance
“…Kovacs et al [28] demonstrated the presence of true corticotroph hyperplasia preceding adenoma formation in a patient with well-defined Nelson’s syndrome. The same mechanism may account for the high ACTH levels and suspected pituitary microadenoma in our patient and in other CAH patients who underwent bilateral adrenalectomy, followed by enhanced ACTH secretion that was not suppressed by intensified glucocorticoid medication [29], and developed pituitary adenoma [30]. …”
Section: Discussionsupporting
confidence: 52%
“…Kovacs et al [28] demonstrated the presence of true corticotroph hyperplasia preceding adenoma formation in a patient with well-defined Nelson’s syndrome. The same mechanism may account for the high ACTH levels and suspected pituitary microadenoma in our patient and in other CAH patients who underwent bilateral adrenalectomy, followed by enhanced ACTH secretion that was not suppressed by intensified glucocorticoid medication [29], and developed pituitary adenoma [30]. …”
Section: Discussionsupporting
confidence: 52%
“…Bilateral TART associated with large adrenal rest tumor located in the perirenal region was reported in an adult CAH patient with known HSD3β2 mutation (5). However, TART development in infants/children has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Przed tą separacją komórki kory nadnerczy mogą przylgnąć do gonad i dalej wędrować razem z jądrami. Dlatego też resztki tkanki nadnerczowej można wykryć na drodze normalnego zstępowania jądra [3,10,11,19,[21][22][23][24][25][26].…”
Section: Testicular Adrenal Rest Tumor (Tart)unclassified